Economic Perspectives on Farm Biosecurity: Stakeholder Challenges and Livestock Species Considerations - Mehmedi, Blerta; Iatrou, Anna Maria; Yildiz, Ramazan; Lamont, Kate; da Costa, Maria Rodrigues; De Nardi, Marco; Allepuz, Alberto; Niine, Tarmo; Niemi, Jarkko K.; Saegerman, Claude (MDPI, 2025)
Livestock farm biosecurity is crucial for animal health and economic sustainability, however uneven adoption/implementation across diverse livestock species and production systems persists. To improve uptake of biosecurity, it is necessary to identify critical economic behavioural, and systematic barriers, and to outline practical drivers. Perceived high costs, labour/time burdens, and uncertain benefits can suppress private investment, while poorly designed indemnities can create moral hazard. Conversely, targeted subsidies, risk-based insurance, and market standards (e.g., certification and procurement) can incentivise implementation. Knowledge and trust gaps, especially in smallholder and backyard settings, further limit compliance. Participatory, and context-specific training led by field veterinarians consistently outperforms top–down messaging, with effective element including: simple, low-cost “easy wins”, tiered checklists, and decision-support tools to help embed routines and demonstrate the value of biosecurity. Integrating clear cost–benefit evidence, incentive-based tools, and co-designed training can transform biosecurity from a perceived practical and cost burden into a resilient, profitable practice that delivers public-good benefits for animal health, trade, and One Health across Europe and beyond.
Keywords: biosecurity practices; financial motivation; cost–benefit evaluation; risk-based schemes; stakeholder education